H.I.A.S. a protective gear integrated with an alarming device and safety signal lights for bike commuters - Ledesma, Andrej Arni Esquillo; de la Peña, Fortunato Jr. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
The occurence of bicycle-vehicle collisions in the Philippines have been an issue for the past couple of years. Since there are no proper infrastructures and facilities to support the biking community, cyclist tend to risk their safety while they are on the road. The aim of this research is to develop a product that will, if not to totally resolve the issue, significantly lessen the occurence of bicycle related accidents.
Thesis (Bachelor of Fine Arts (Industrial Design))--University of the Philippines Diliman
Bibliography : leaves 42-43.
Keywords: Bicycles -- Safety measures; Bicycles -- Gearing